2015
DOI: 10.4141/cjas-2015-013
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Field study of air ammonia concentrations in Ontario dairy calf housing microenvironments

Abstract: . 2015. SHORT COMMUNICATION: Field study of air ammonia concentrations in Ontario dairy calf housing microenvironments. Can. J. Anim. Sci. 95: 539Á542. The objective of this study was to measure the ammonia concentrations in the microenvironment of the calf housing area on a sample of commercial dairies in Ontario under typical management conditions. Two approaches were used to measure ammonia concentrations: (1) weekly on four farms for a period of 8 wk and (2) one-time samples were taken from the calf areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Moreover, the limited numbers of herds may also be a limitation of the present study. Interestingly, ammonia levels were consistently low throughout our study and even lower than previously reported in winter (Seedorf and Hartung, 1999;Lago et al, 2006) or in summer (Kaufman et al, 2015). The inflammatory effect of high levels of ammonia on the respiratory tract has been mentioned in calves (Dewes and Goodall, 1995), but in a more recent Swedish study at the herd-level ammonia levels <6 ppm were counterintuitively associated with an increased odd of respiratory disease (odds ratio = 2.46; 95% CI = 1.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Moreover, the limited numbers of herds may also be a limitation of the present study. Interestingly, ammonia levels were consistently low throughout our study and even lower than previously reported in winter (Seedorf and Hartung, 1999;Lago et al, 2006) or in summer (Kaufman et al, 2015). The inflammatory effect of high levels of ammonia on the respiratory tract has been mentioned in calves (Dewes and Goodall, 1995), but in a more recent Swedish study at the herd-level ammonia levels <6 ppm were counterintuitively associated with an increased odd of respiratory disease (odds ratio = 2.46; 95% CI = 1.…”
Section: Discussioncontrasting
confidence: 49%
“…The ammonia level was also recorded at the same sites using a handheld ammonia analyzer (GasAlertNH3, Honeywell Analytics, Lincolnshire, IL) with a range detection of 0 to 50 ppm. An increased ammonia level was considered if ammonia concentration was ≥5 ppm to take into account recent recommendations (between 3.5 and 7 ppm) in Canadian dairy farms (Kaufman et al, 2015).…”
Section: Assessment Of Air Draft Temperature Hygrometry and Ammoniamentioning
confidence: 99%
“…The document only states that insulation, heating and ventilation of the buildings must ensure that air circulation, dust level, temperature, relative air humidity and noxious gas concentrations need to be kept within limits which are not harmful to the calves. Proper ventilation, allowing the availability of fresh and clean air and the removal of dusts, gases, pollutants, moisture and microbes helps to optimise calf health [ 11 , 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ammonia inside the calf pen is very important as well. Calves are likely to be more sensitive to environmental irritants, such as ammonia, than adult cattle [ 11 ]. Ammonia concentration depends on the accumulation of urine and faeces, which emphasises the need for regular cleaning and provision of dry bedding, together with adequate ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation